Book Review on "ETpedia: 1,000 ideas for English language teachers" - İsmail Yaman (Sakarya University, 2016)
ETpedia: 1,000 ideas for English language teachers apparently appears to be a useful reference book with a number of pros. First of all, the appearance that welcomes readers is quite striking and attractive. This book may bring love at first sight for the readership with its interesting coil binding and colourful design. What is more, the content and organization of the book do not disappoint the readers. With 1,000 to-the-point ideas offered through the smart 10-item approach, the book will most probably live up to the expectations of most English language teachers. It touches on almost every point likely to be experienced by teachers. Alongside ideas aiming to ease the teaching of macro- and micro-skills in English classes, there are numerous strategies to handle lessons in case of different scenarios. For instance, when a teacher is unexpectedly asked to deliver a lesson on behalf of one of his/her colleagues, s/he can easily benefit from the theme-based activities provided in Section 3. As for the other sections, their content will most probably serve as invaluable pieces of information for a teacher who encounters difficulties during his/her attempts to help students develop a specific skill, or faces problems with classroom management, or wants to promote his/her field-related expertise.